Genome Sequencing and Assembly Strategies and a Comparative Analysis of the Genomic Characteristics in Penaeid Shrimp Species - Yuan, Jianbo; Zhang, Xiaojun; Li, Fuhua; Xiang, Jianhai (Frontiers in Genetics, 2021)
Penaeid shrimp (family Penaeidae) represents one of the most economically and ecologically important groups of crustaceans. However, their genome sequencing and assembly have encountered extreme difficulties during the last 20 years. In this study, based on our previous genomic data, we investigated the genomic characteristics of four penaeid shrimp species and identified potential factors that result in their poor genome assembly, including heterozygosity, polyploidization, and repeats. Genome sequencing and comparison of somatic cells (diploid) of the four shrimp species and a single sperm cell (haploid) of Litopenaeus vannamei identified a common bimodal distribution of K-mer depths, suggesting either high heterozygosity or abundant homo-duplicated sequences present in their genomes. However, penaeids have not undergone whole-genome duplication as indicated by a series of approaches. Besides, the remarkable expansion of simple sequence repeats was another outstanding character of penaeid genomes, which also made the genome assembly highly fragmented. Due to this situation, we tried to assemble the genome of penaeid shrimp using various genome sequencing and assembly strategies and compared the quality. Therefore, this study provides new insights about the genomic characteristics of penaeid shrimps while improving their genome assemblies.